A new version of energy for involute of slant helix with bending energy in the Lie groups - Körpınar, Talat (UNIV ESTADUAL MARINGA, PRO-REITORIA PESQUISA POS-GRADUACAO, 2019)
In this paper, we study energy of involute curves for slant helix in the Lie group. With this new representation, we illistrate some figures of energy by elastica. Finally, we have an original and satisfactorily connection between energy of the curve on Lie groups.
Keywords: energy; lie group; involute curves